2005
DOI: 10.1099/jmm.0.46191-0
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Chlamydophila pneumoniae infection in long-term care facilities and an affiliated hospital

Abstract: This paper reports an outbreak of Chlamydophila pneumoniae infection in long-term care facilities and an affiliated hospital. The outbreak involved rapid spread of infection, and was inconsistent with several outbreaks experienced among younger populations. In addition, there were differences in the incidences among facilities and the affiliated hospital in relation to mean age. Our findings indicate that it is possible that elderly residents may be more susceptible to acquiring this infection. Physicians and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
(30 reference statements)
2
3
1
Order By: Relevance
“…They speculated that one reason for the high frequency was an outbreak of C. pneumoniae infection in a nursing home. Outbreaks of C. pneumoniae in nursing homes and long-term care facilities reported in previous studies support this assumption (31,32). In fact, during our study period, an outbreak of C. pneumoniae occurred among residents in a care home.…”
Section: Discussionsupporting
confidence: 71%
“…They speculated that one reason for the high frequency was an outbreak of C. pneumoniae infection in a nursing home. Outbreaks of C. pneumoniae in nursing homes and long-term care facilities reported in previous studies support this assumption (31,32). In fact, during our study period, an outbreak of C. pneumoniae occurred among residents in a care home.…”
Section: Discussionsupporting
confidence: 71%
“…This report summarizes the largest C. pneumoniae outbreak confirmed by qPCR. The long duration of the outbreak (over 4 months) is consistent with C. pneumoniae outbreaks described in military barracks [17,18] and contrasts with the shorter duration (1-2 months) often seen in long-term care facilities [6,7]. The attack rates seen in this prison were lower than the median reported among long-term care facilities (46%), possibly due to lower prevalence of comorbid conditions as this facility was rated care level 2 by the BOP, and inmates did not have medical conditions that required more than routine appointments for monitoring [8].…”
Section: Discussionsupporting
confidence: 72%
“…Chlamydia pneumoniae is endemic world-wide. Outbreaks occur periodically and without a clear seasonal pattern, primarily in close-contact settings among high-risk populations such as in long-term care facilities [6][7][8]. Chlamydia pneumoniae is frequently detected alongside other respiratory pathogens, making its role as a primary disease-causing pathogen unclear [9][10][11].…”
mentioning
confidence: 99%
“…20,22 Outbreaks of respiratory illness due to atypical bacteria, specifically C. pneumoniae, have been reported in nursing homes worldwide and are often characterized by high attack rates due to its airborne transmission. [39][40][41][42][43][44][45][46][47][48][49] Thus, the high rate of C. pneumoniae among all patients in the 2008 and 2010 Maruyama et al studies could be the result of a C. pneumoniae outbreak. Yet in their 2010 study, Maruyama and colleagues reported an even distribution of atypical bacteria at Kinan General Hospital during the June 2004 and May 2005 study period.…”
Section: Discussionmentioning
confidence: 99%